2021
DOI: 10.1002/ente.202000881
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Deviations between Spatially Resolved and Homogenized Cathode Models of Lithium‐Ion Batteries

Abstract: Porous electrode models are essential for inexpensively predicting the performance and lifetime of lithium‐ion batteries. Physics‐based models range from microscopic 3D models, which spatially resolve the microstructural characteristics of all phases in porous electrodes, to reduced and computationally effective models, which do not resolve the microstructure. The homogenized Newman model, also known as the pseudo‐2D (P2D) model, is well established and widely used. However, the necessary simplification shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…First, we assumed diffusion paths to be longer than the primary particle radius by a factor of 1.5. Schmidt et al [22] . suggested this assumption if part of the active material particle surface is blocked.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we assumed diffusion paths to be longer than the primary particle radius by a factor of 1.5. Schmidt et al [22] . suggested this assumption if part of the active material particle surface is blocked.…”
Section: Methodsmentioning
confidence: 99%
“…First, we assumed diffusion paths to be longer than the primary particle radius by a factor of 1.5. Schmidt et al [22] suggested this assumption if part of the active material particle surface is blocked. This is the case for hierarchically structured electrodes, since the primary particles are sintered together.…”
Section: Hierarchically Structured Half-cell Modelmentioning
confidence: 99%
“…Additionally, it resolves each variable in the porous geometry so one can model their spatial distributions (e.g. to describe the ion flow around the particles), and any further reduction of this model can cause deviations in the predicted values [116]. However, this does not mean it is the best model to use in practical applications because it poses two main challenges.…”
Section: Microscale Modelmentioning
confidence: 99%
“…First, this model is extremely computationally expensive which means that it is not viable for most real applications [116]. On top of that, the full microscale geometry of the battery is required (e.g.…”
Section: Microscale Modelmentioning
confidence: 99%
“…The simulations were parametrized with measured EIS data in the frequency domain and were validated with charging and discharging processes in the time domain. Nonetheless, nonuniformity in complex electrodes cannot be considered in those macroscopically homogeneous models . Another type of modeling was employed to simulate EIS behavior with physics-based information. For example, Cho et al used reaction and diffusion that can be analytically calculated for spherical, cylindrical, and platelet particles to obtain the stochastic average EIS behavior of a three-dimensional (3D) complex electrode.…”
Section: Introductionmentioning
confidence: 99%